Assays of D-Amino Acid Oxidase Activity - Rosini, Elena; Caldinelli, Laura; Piubelli, Luciano (Frontiers in Molecular Biosciences, 2018)
D-amino acid oxidase (DAAO) is a well-known flavoenzyme that catalyzes the oxidative FAD-dependent deamination of D-amino acids. As a result of the absolute stereoselectivity and broad substrate specificity, microbial DAAOs have been employed as industrial biocatalysts in the production of semi-synthetic cephalosporins and enantiomerically pure amino acids. Moreover, in mammals, DAAO is present in specific brain areas and degrades D-serine, an endogenous coagonist of the N-methyl-D-aspartate receptors (NMDARs). Dysregulation of D-serine metabolism due to an altered DAAO functionality is related to pathological NMDARs dysfunctions such as in amyotrophic lateral sclerosis and schizophrenia. In this protocol paper, we describe a variety of direct assays based on the determination of molecular oxygen consumption, reduction of alternative electron acceptors, or α-keto acid production, of coupled assays to detect the hydrogen peroxide or the ammonium production, and an indirect assay of the α-keto acid production based on a chemical derivatization. These analytical assays allow the determination of DAAO activity both on recombinant enzyme preparations, in cells, and in tissue samples.